Functional activity of neutrophils and systemic inflammatory response of Down's syndrome patients with periodontal disease - Isabelle Rodrigues Freire; Sandra Maria Herondina Coelho Ávila Aguiar; Sandra Helena Penha de Oliveira (Universidade Estadual de Campinas, 2015)
Periodontal disease (PD) is characterized as an inflammatory process that compromises the support and protection of the periodontium. Patients with Down's syndrome (DS) are prone to develop PD. Neutrophils (NE) are the first line of defense against infection and their absence sets the stage for disease. Aim: To compare the activity and function of NE in the peripheral blood from DS patients with and without PD, assisted at the Center for Dental Assistance to Patients with Special Needs affiliated with the School of Dentistry of Araçatuba, Brazil. Methods: Purified NE were collected from peripheral blood of 22 DS patients. NE were used to detect the 5-lypoxigenase (5-LO) expression by RT-PCR. Plasma from peripheral blood was collected to measure tumor necrosis factor-a (TNF-α) and interleukin-8 (IL-8) by ELISA and nitrite (NO3 ) using a Griess assay. Results: Data analysis demonstrated that DS patients with PD present high levels of TNF-a and IL-8 when compared with DS patients without PD. However, there was no statistically significant difference in the levels of NO3 production between the groups. The levels of the inflammatory mediator 5-LO expression increased in DS patients with PD. Conclusions: According with these results, it was concluded that TNF-α and IL-8 are produced by DS patients with PD. Furthermore, DS patients with PD presented high levels of 5-LO expression, suggesting the presence of leukotriene B4 (LTB4 ) in PD, thus demonstrating that the changes in NE function due to the elevation of inflammatory mediators contribute to PD.